97 things every java programmer should know collective wisdom from the experts - Henney, Kevlin; Gee, Trisha J. (O'Reilly Media, Incorporated, 2020)
If you want to push your Java skills to the next level, this book provides expert advice from Java leaders and practitioners. You'll be encouraged to look at problems in new ways, take broader responsibility for your work, stretch yourself by learning new techniques, and become as good at the entire craft of development as you possibly can. Edited by Kevlin Henney and Trisha Gee, 97 Things Every Java Programmer Should Know reflects lifetimes of experience writing Java software and living with the process of software development. Great programmers share their collected wisdom to help you rethink Java practices, whether working with legacy code or incorporating changes since Java 8.
Includes index. - Print version record
Keywords: Java (Computer program language); Java (Langage de programmation)